Pertumbuhan dan Produksi Rumput Setaria (Setaria splendida Stapf) sebagai Pakan Ternak Ruminansia pada Tanah Ultisol dengan Penambahan Pupuk Kotoran Kambing - Suningsih, Nining; Noprida, Hayatun; Feriyanto, Feriyanto (Seminar Nasional Lahan Suboptimal, 2019)
Suningsih N, Noprida H, Feriyanto F. 2019. Growth and production of setaria splendida grass in ultisol soils with the addition of goat manure. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 201-210.  Palembang: Unsri Press. Setaria grass is one of the superior types of grass for Ruminants which has not been widely cultivated due to limited planting land. The purpose of this study was to determine the growth and first  production of Setaria grass planted on ultisol soil with the addition of Goat Manure Fertilizer (GMF). The study design used a Randomized Block Design (RBD) consisting of 6 treatments and 4 replications. The treatment is S0 = Ultisol Land, S1 = S0 + GMF 100 g/Polybag, S2 = S0 + GMF 150 g/Polybag, S3 = S0 + GMF 200 g/Polybag, S4 = S0 + GMF 250 g/Polybag, and S5 = S0 + GMF 300 g/Polybag. The variables observed were Plant Height, Number of Tiller, Fresh Weight, and Dry Weight. The data obtained were analyzed for variance (ANOVA) and further tests were carried out using the DMRT Advanced Test. The results showed that the treatment of GMF addition on Ultisol soil had a very significant effect (P <0.01) on Setaria grass height, Number of tillers, Fresh weight production, and Production of dry weight. Advanced Test Results DMRT shows the highest Setaria grass shown by S5 treatment (85.58 cm), the highest number of tillers indicated by treatment S5 (20.42 tillers), the heaviest fresh weight of Setaria grass shown by S5 (225.33 g), and weight the heaviest dryness is also indicated by S5 (46.50 g). The conclusion of this study is that the growth and production of Setaria grass planted on Ultisol soil significantly increased with the increasing dose of goat manure fertilizer.Keywords: growth, production, goat manure fertilizer, setaria grass, ultisol land